IMPLEMENTASI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV SD - Safitri, Erika; Hendratno; Luchaidah; Mahallisa Dyah Pristanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve collaboration skills through the application of the Team Games Tournament (TGT) model in the science content of grade IV SDN Kedurus III, from the initial data it was found that the level of collaboration between students was still low, because students did not do enough discussion activities which resulted in difficulties in grouping. The type of research is Classroom Action Research (CAR) which was carried out for 2 cycles with the Kemmis & Mc. Taggart model, namely Planning, (2) Implementation, (3) Observation and (4) Reflection of Results. The subjects of the study were 26 students. The data analysis techniques used in this study were descriptive quantitative and qualitative. The results of the study showed that the percentage of collaboration skills in the pre-cycle was 12 students 46.1% with a fairly collaborative category, in cycle I there were 14 students 57.7% with a good collaborative category and in cycle II there were 21 students (80.8%) with a very collaborative category. Based on these data, there is an increase in each cycle, thus the application of the Team Games Tournament (TGT) model can improve students' collaboration skills.